Optimization of Tesla Valve Cooling Channels for High-Efficiency Automotive PMSM - Ning Zhou; Huawei Wu; Zhi Li; Yubo Ma; Shaokang Lu (World Electric Vehicle Journal)
Efficient heat dissipation remains a critical challenge in the research and development of automotive permanent magnet synchronous motors. In this study, a Tesla valve cooling channel is innovatively designed, and a corresponding flow model is established using computational fluid dynamics (CFD) simulations. The effects of the spacing between adjacent Tesla valves, the number of stages, and inlet velocities on motor temperature rise and pressure drop within the channel are analyzed under varying flow directions. A comprehensive evaluation of 25 simulation samples reveals that the reverse flow Tesla valve-type channel, with an inlet velocity of 1 m/s, 90 mm spacing, and 16 stages, achieves an optimal balance between cooling performance and energy consumption. Compared to the conventional spiral waterway design, this configuration reduces the maximum temperature and temperature difference by 1.5% and 2.2%, respectively, while maintaining a relatively low pressure drop. Additionally, the structure enhances the coolant’s heat exchange capacity, effectively lowering the peak temperature of the motor. These findings provide valuable insights for advancing motor cooling technologies.